2019
DOI: 10.2319/090518-651.1
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the gubernacular canal and its attachment to the dental follicle may indicate an abnormal eruption status

Abstract: Objectives: To evaluate and compare the detection of gubernacular canals (GC) and their characteristics in normal and abnormal tooth eruption. Materials and Methods: Patients with unerupted teeth were classified according to sex and age. Each tooth was classified according to dental group, eruption status, formation status, angulation, and GC detection. The opening of the GC in the alveolar crest and the attachment sites in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(55 citation statements)
references
References 16 publications
4
40
0
11
Order By: Relevance
“…Gaˆeta-Araujo H et al reported that the most communal attachment site of GC was to the occlusal side of the dental sac of the unerupted tooth (93.2%) and was classified as a usual attachment. These findings were in agreement with our case, where we also found the GT to be attached to the occlusal aspect of the dental sac of the supernumerary tooth 25 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Gaˆeta-Araujo H et al reported that the most communal attachment site of GC was to the occlusal side of the dental sac of the unerupted tooth (93.2%) and was classified as a usual attachment. These findings were in agreement with our case, where we also found the GT to be attached to the occlusal aspect of the dental sac of the supernumerary tooth 25 .…”
Section: Discussionsupporting
confidence: 93%
“…Oda M. et al 24 suggested that the presence of and contact with the gubernacular tract (GT) should be added as a characteristic CT finding of some types odontogenic masses including dentigerous cysts, calcifying odontogenic cysts (Gorlin Cyst), odontomas, Adenomatoid Odontogenic Tumor and perhaps others. Moreover, they concluded that dentists should pay more attention to the association between the GT and odontogenic masses 24,25 . Our case demonstrated an association between the GT and the odontoma where the odontoma was inside the GT of the supernumerary tooth with the same spatial relationship in agreement with Oda M. et al 24 which reports that the majority of odontoma cases (about 70%) detected with CBCT were inside the GT of the unerupted teeth (Figure 2d).…”
Section: Discussionmentioning
confidence: 99%
“…Increased RANKL in the coronal dental follicle induced by isorhamnetin 3-o-neohesperid further promoted crown-covered bone resorption in vivo. The dental follicle is essential for tooth eruption 30,31 . Disturbance in the functions of dental follicles results in delayed tooth eruption in cleidocranial dysplasia (CCD) patients 32,33 .…”
Section: Discussionmentioning
confidence: 99%
“…Histologically, the GD is composed of a fibrous band called the gubernacular cord (GCo), which typically consists of the epithelial remnants of the dental lamina, as well as a bony channel around the GCo connecting the pericoronal follicular tissue of the successional or accessional tooth with the overlying gingiva that opens to the alveolar bone crest [ 1 , 2 , 3 ]; this bony channel is known as the gubernaculum tract (GT) or gubernacular canal. However, few clinical studies have focused on the presence, appearance, and importance of these structures, which could be related to the normal eruption of teeth [ 4 , 5 , 6 ]. One possible explanation for the lack of studies is that the GT is difficult to visualize on two-dimensional radiographs, such as dental and panoramic radiographs, because it is very thin (1–3 mm in diameter) and therefore often superimposed on images of deciduous teeth and trabeculae [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, few clinical studies have focused on the presence, appearance, and importance of these structures, which could be related to the normal eruption of teeth [ 4 , 5 , 6 ]. One possible explanation for the lack of studies is that the GT is difficult to visualize on two-dimensional radiographs, such as dental and panoramic radiographs, because it is very thin (1–3 mm in diameter) and therefore often superimposed on images of deciduous teeth and trabeculae [ 4 , 5 , 6 ]. Therefore, the GD has not received sufficient attention in dental fields such as pediatric dentistry and oral and maxillofacial radiology.…”
Section: Introductionmentioning
confidence: 99%